Design and implementation of an X-band passive RFID tag - Senadeera, Praharshin M.; Xie, Zhijian; Do?an, Numan S.; Savcı, Hüseyin Şerif (Institute of Electrical and Electronics Engineers Inc., 2020)
This paper presents a novel fully integrated energy harvester, multi-stage RF-DC rectifier, mode selector, RC oscillator, LC oscillator, and X-band power amplifier implemented in IBM 0.18-µm RF CMOS technology. We investigated different matching schemes, antennas, and rectifiers with focus on the interaction between building blocks. Currently the power amplifier gives the maximum output power of 5.23dBm at 9.1GHz.The entire RFID tag circuit was designed to operate in low power consumption. Voltage sensor circuit which generates the enable signal was designed to operate in very low current. All the test blocks of the RFID tag were tested. The smaller size and the cost of the RFID tag are critical for widespread adoption of the technology. The cost of the RFID tag can be lowered by implementing an on-chip antenna. We were able to develop, fabricate, and implement a fully integrated RFID tag in a smaller size (3 mm X 1.5 mm) than the existing tags. With further modifications, this could be used as a commercial low cost RFID tag.
Keywords: RFID; RF-DC Rectifier; X-Band Power Amplifier; RC Oscillator; Energy Harvester; Passive RFID Tags